Role-playing in Shakespeare - Van Laan, Thomas F. (Heritage., 1978)
The wide scope of this enquiry, taking in all of Shakespeare's plays, and the thoroughness with which Van Laan has pursued his argument provide a coherent and illuminating perspective on two of the most intriguing qualities of Shakespeare's work as a whole: the sense of continuity and the sense of an underlying unity within such great variety.